THE ROLE OF G. SKOVORODA IN THE CULTURAL DEVELOPMENT OF SLOBOZHANSHCHYNA0 - Паньок, Тетяна (New Collegium, 2020)
The research is associated with a comprehensive study of icon painting in Sloboda Ukraine, an attempt at historical justification and objective interpretation of icon painting artifacts of the Baroque period in the seventeenth and eighteenth century from the point of view of the style formation, icon painting features and identification of regional specificity as an integral part of the historically determined artistic system and artistic phenomenon of Ukrainian culture. The research methodology is the use of art-historical, comparative, and historical and logical methods. its methodological framework is the principles of systematicity and historicism. icon painting in Sloboda Ukraine is studied as a phenomenon of national culture, a phenomenon of a certain cultural and historical situation interacting with social, historical and cultural factors. The scientific novelty of the research is that it is for the first time in Ukrainian art history that the evolution of icon painting in Sloboda Ukraine is studied and the concept of the cultural and historical context of the origin and development of this artistic phenomenon is extended based on primary sources. The place that the Sloboda Ukraine icons occupy in the general development of Ukrainian icon painting has been determined for the first time. The analysis of the artistic and imagery system of icon painting in Sloboda Ukraine has shown that the Baroque style was dominant in the period studied, as well as in the whole Ukrainian art; it was best suited for the national character and embodied the Ukrainian mentality. The spread of the Baroque style in the region was determined by the peculiarities of the spiritual life of the period, its secularization. Referring to the innovations of Western art brought by settlers combined with the original local «soil,» intertwining with the Ukrainian sacral painting traditions in the works of various local schools, as well as with the post-Byzantine tradition, which led to the original interweaving of archaisms and innovations.